The Role of Financial Performance in Mediating the Economic Effects of Diversification on Sustainability Outcomes - Sardju, Fitriani; Sinen, Kasim; Fajriyanti, Nurul; Aksan, Ismul (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to examine and analyze the effect of diversification on sustainability performance, with financial performance acting as a mediating variable. The research was conducted on Islamic Commercial Banks (BUS) in Indonesia that were registered with the Financial Services Authority (OJK) during the period 2020–2022. The sampling method employed was purposive sampling. This study is motivated by previous research on the performance of Islamic banks in Indonesia, which has predominantly focused on financial or business outcomes. In response, several international scholars in Islamic banking have proposed a more comprehensive approach to measuring performance through the Islamicity Performance Index. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of WarpPLS 7.0 software. The findings reveal that diversification has a direct effect on sustainability performance and also exerts an indirect effect through financial performance as a mediating variable. Sustainability performance represents a crucial first step toward proactive innovation for Islamic banks, enabling them to enhance their competitiveness in an increasingly dynamic banking sector. Diversification serves as a strategic effort to improve the sustainability performance of Islamic banks in Indonesia. The main limitation of this study is the relatively short observation period and the narrow focus on Islamic banks, which still represent a small segment of the financial industry. Future research is recommended to expand the sample to include other Sharia-based companies across various sectors.